The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1081/ma-200026151
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofN‐Methyl Imidazole and Dimethyl Pyrazole Ligands on Polymerization of di(2,4,6‐Trichlorophenolato)Cu(II)/Co(II) Complexes in Solid State

Abstract: Polymerization of 2,4,6-trichlorophenol (TCPH) was achieved through the thermal decomposition of the copper and cobalt complexes of TCPH with N-containing ligands [N-methyl imidazole (NMIz) and 3,5-dimethyl pyrazole (DMPz)]. The structural analysis of the complexes was performed by using Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), mass (MS), UV-VIS, diffuse reflectance (DRS) and electron spin resonance (ESR) spectroscopies, magnetic susceptibility balance and elemental analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Co(TBP) 2 (NMIZ) 2 complexes (Figure 2(b)) showed a sharp exothermic peak at 132.5 • C and an endothermic peak at 184.53 • C ,whereas Ni(TBP) 2 (NMIZ) 2 (Figure 2(c)) showed a single sharp exothermic peak at 143.93 • C. The exothermic peaks are attributed to the new bond formation during polymerization. This vision was previously supported by DSC-IR study (16) which showed the polymer formation at the peak temperature and the increase in the % conversions during polymerization beyond the exothermic peak temperatures. In order to investigate the origin complexes revealed endotherms that were close to the values reflected in thermograms of the original complexes ( Figure 2).…”
Section: Ni(tbp) 2 (Nmiz)mentioning
confidence: 70%
See 1 more Smart Citation
“…Co(TBP) 2 (NMIZ) 2 complexes (Figure 2(b)) showed a sharp exothermic peak at 132.5 • C and an endothermic peak at 184.53 • C ,whereas Ni(TBP) 2 (NMIZ) 2 (Figure 2(c)) showed a single sharp exothermic peak at 143.93 • C. The exothermic peaks are attributed to the new bond formation during polymerization. This vision was previously supported by DSC-IR study (16) which showed the polymer formation at the peak temperature and the increase in the % conversions during polymerization beyond the exothermic peak temperatures. In order to investigate the origin complexes revealed endotherms that were close to the values reflected in thermograms of the original complexes ( Figure 2).…”
Section: Ni(tbp) 2 (Nmiz)mentioning
confidence: 70%
“…Up to date polymerization of halogenated phenols has been studied with transition and inner transition metal complexes with various amine ligands through various decomposition techniques which are electroinitiation in solution (13), thermal decomposition in solid state (14) and in solution (15 (16). Thus, authors considered the use of N-methylimidazole ligand as a powerful approach to archive better percent conversions.…”
Section: Introductionmentioning
confidence: 99%